Improving the efficiency of grinding-classification and gravity separation. The use of Rheology Modifier - F. J. Sotillo (Instituto de Ingenieros de Minas del Peru, 2007)
The reduction in energy consumption has been always important for beneficiation plants. Also gravity separation processes have gained lately great importance due to environmental concerns, especially in the gold and silver Industries. In this sense, the paper point out how to reduce the energy consumption in grinding, and increase efficiency in both grinding and gravity separation are of utmost importance to optimize the use of the country’s resources. For these purposes, chemical additives, such as rheology modifiers have shown great potential, and deserved careful consideration.